2009
DOI: 10.1096/fj.09-135624
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor ligands induce polymorphonuclear leukocyte migration: key roles for leukotriene B4and platelet‐activating factor

Abstract: Activation of toll-like receptors (TLRs) and polymorphonuclear leukocyte (PMN) accumulation at infection sites are critical events of host defense. The involvement of leukotriene (LT) B(4) and platelet-activating factor (PAF) in TLR ligand-induced activation of inflammatory cell functions is essentially unknown. Using an in vitro model of human PMN migration through human endothelial cell monolayers, we demonstrate that prototypic ligands of TLR1/2, 2/6, 3, 4, 5, and 7/8 promote PMN migration, an effect marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 57 publications
4
24
0
1
Order By: Relevance
“…Previous studies have shown an association between TLR signaling and lipid mediators [16, 37]. Our results further indicate that this interaction may lead to NFkB activation, possibly through TLR2, and LTB 4 production.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies have shown an association between TLR signaling and lipid mediators [16, 37]. Our results further indicate that this interaction may lead to NFkB activation, possibly through TLR2, and LTB 4 production.…”
Section: Discussionsupporting
confidence: 83%
“…Signaling through LTB 4 induces leukocyte accumulation [13], microbial ingestion [14], and killing [15]. LTB 4 also plays a critical role in human neutrophil migration induced by Toll-like receptor (TLR) stimulation [16]. TLR ligands prime LTB 4 production and neutrophil migration [17], and the LTB 4 receptor, B leukotriene receptor 1 (BLT1), is responsible for mediating these effects [18].…”
mentioning
confidence: 99%
“…Corroborating this hypothesis was the observation that prophylactic treatment of experimental animals (rats) with AFL also showed inhibition of neutrophil migration into the intraperitoneal cavity induced by carrageenan (Batista-Lima et al, 2001). The migration of neutrophils into the peritoneal cavity of rats induced by carrageenan is dependent on the release of eicosanoids and chemotactic agents such as leukotriene B4 and/or IL-8, respectively, produced by mast cells and/or resident macrophages (Lefebvre et al, 2010, Nakagome & Nagata, 2011. Taken together the results support the hypothesis that AFL treatment is modulating cytokines as well as antiinflammatory mediator effects.…”
Section: Anti-inflammatory Activity Of Cissampelos Sympodialissupporting
confidence: 71%
“…On the other hand, failure to produce adequate amounts of inflammation-resolving and tissue repair factors at the most appropriate time and stage of sepsis may prove to be fatal. In this context, it is noteworthy that TLRs regulate free radical generation as well as macrophage and leukocyte function and modulate eicosanoid synthesis, and thus play a critical role in inflammation and the immune response [810]. It is likely that initial excess stimulation of TLRs leads to exaggerated production of free radicals, pro-inflammatory eicosanoids and cytokines that produce the initial hyperinflammatory response which if followed by exacerbated negative feedback control could lead to progressive development of immunosuppression seen in sepsis.…”
Section: Introductionmentioning
confidence: 99%